Impact of bariatric surgery on circulating PCSK9 levels as a marker of cardiovascular disease risk: a meta-analysis - Tannaz Jamialahmadi; Maciej Banach; Wael Almahmeed; Prashant Kesharwani; Amirhossein Sahebkar (Archives of Medical Science, 2022)
Introduction This systematic review and meta-analysis focuses on PCSK9 changes in obese patients following bariatric surgery.